Interplay of sketching & prototyping in early stage product design. Issue 3 (2nd October 2018) - Bao, Qifang; Faas, Daniela; Yang, Maria
Abstract: Research suggests that, for the design of simple mechanisms, sketching and prototyping are somewhat interchangeable in terms of their influence on idea quantity and quality. This study explores whether this interchangeability holds true for a consumer product design activity. Three conditions are compared: sketching only, prototyping only, and free prototyping & sketching. Eighteen novice designers participated in a one-hour individual design activity. Their resulting design ideas were evaluated by both design experts and potential users. A design evaluation metric, idea distance, is proposed to measure the breadth and depth of design space exploration. Results showed that individuals who only sketched, on average, generated more ideas, explored broader design space, and had more novel final designs. However, participants who were allowed to both sketch and build prototypes explored the design space in more depth and tended to have final ideas that were perceived as more creative. Individuals who only prototyped generated designs that were perceived to be aesthetically more pleasing and performed better functionally. Exploring broader design space was found to correlate with more unique ideas. However, exploring too broad a design space reduced the depth of idea exploration, and was negatively linked to the functional performance of the final designs.